Adição de dejetos de bovinos de corte em processos biológicos de estabilização de cama de ovinos. - Cestonaro, Taiana (2013)
Sheep litter has in its composition manures incorporated to rice husk, which is a lignocellulosic material. Materials with this characteristic are stabilized for longer period of time and have restrictions on decomposing since they present strong fractions that can, sometimes, be inaccessible to micro-organisms. Some alternatives have been used in order to easy these nutrients recycling, for example its ordinary mixing with another residue. Thus, this essay aimed at evaluating vermicomposting, composting and anaerobic co-digestion applied to sheep litter mixed with cattle manure in order to provide available conditions to change such residues. Three assays were carried out from five ratios of sheep litter and cattle manure: 0:100, 25:75, 50:50, 75:25 and 100:0, which represented treatments T100, T75, T50, T25 and T0, respectively. The process of vermicomposting was carried out from November 2011 to march 2012. The material has undergone a preparation in order to eliminate toxic composts. Then, 0.88 kg of dry mass and 15 adult worms (Eisenia foetida) were allocated in the vermireactor. The ≥ 45% ash content was the stability parameter adopted in this assay. The composting piles were carried out from April to July 2012 in a covered area of concrete floor. Each pile had 200 kg of dry mass and received manual turnings two times a week during the first month and weekly from then on. Composting was supervised until the piles reached values close to room temperature, when the material was stabilized. The experimental period for anaerobic co-digestion occurred from May to October 2012. An entry mixture diluted with water was made in order to obtain a 5% content of total solids. And for residues fermentation, PVC bench scale bio-digesters were used to storage 6 L volume of such material. An anaerobic co-digestion was carried out in a batch system and observed until the curve of biogas production had decreased. In all assays, the adopted experimental design was completely randomized with univariate and multivariate statistics for data evaluation. The results showed that 50% of cattle manure was necessary in the mixture so that sheep litter could be efficiently absorbed in composting and in anaerobic co-digestion. This ratio generated a compost and biofertilizer with greater stability and content of nutrients as well as provided a larger scale of biogas production. In vermicomposting, the sheep litter showed potential to be used in a ratio up to 75% in mixture with cattle manure for Eisenia foetida specie development. However, greater ratios than 25% have decreased the vermicompost quality and in all assays, the rice husk was not transformed.